Critical Care Nurses’s Knowledge and Attitude Towards Sleep Promoting Interventions Among Critically Ill Patients in Intensive Care Unit - Razali, Maisarah; Fauzi, Rosuzeita; Che Hamzah, Shaharudin Shah (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Sleep promotion in the Intensive Care Unit (ICU) should be a priority because interruptions may prevent patients from getting enough sleep. Inadequate sleep might lead to delirium, anxiety, increased hospital stays, and higher mortalities. Critical care nurses with good knowledge and attitude towards sleep promotion interventions benefit critically ill patients’ quality of care and life. Critical illness, pain, mechanical ventilation, surroundings, and nurses’ activity at night contribute to sleep disturbances in ICU patients. The aim of this study was to determine critical care nurses’ knowledge regarding the physiology of sleep, interventions to promote sleep, attitude towards sleep, and sleep promotion. Methods: A cross-sectional study with a self-administered questionnaire and purposive sampling method was conducted among 109 critical care nurses at the ICU of a teaching hospital. Results: Introduction: Sleep promotion in the Intensive Care Unit (ICU) should be a priority because interruptions may prevent patients from getting enough sleep. Inadequate sleep might lead to delirium, anxiety, increased hospital stays, and higher mortalities. Critical care nurses with good knowledge and attitude towards sleep promotion interventions benefit critically ill patients’ quality of care and life. Critical illness, pain, mechanical ventilation, surroundings, and nurses’ activity at night contribute to sleep disturbances in ICU patients. The aim of this study was to determine critical care nurses’ knowledge regarding the physiology of sleep, interventions to promote sleep, attitude towards sleep, and sleep promotion. Methods: A cross-sectional study with a self-administered questionnaire and purposive sampling method was conducted among 109 critical care nurses at the ICU of a teaching hospital. Results: The mean score knowledge of critical care nurses was 4.72 (± 1.92), attitude towards sleep was 18.57 (± 3.56), and intervention towards sleep promotion was 70.00 (± 12.00). A significant correlation was observed between knowledge and attitude (p < 0.05, r = 0.22) and between attitude and intervention (p < 0.05, r = 0.32), indicating a modest correlation. Moreover, a significant association was noted between years of experience and attitude and intervention (p < 0.05). Conclusion: Critical care nurses’ knowledge, attitudes, and interventions were poor; hence, they need to improve their knowledge, attitude, and interventions. The significance of sleep promotion and factors leading to critical care nurses in Malaysia not promoting sleep among ICU patients needs to be rectified. The mean score knowledge of critical care nurses was 4.72 (± 1.92), attitude towards sleep was 18.57 (± 3.56), and intervention towards sleep promotion was 70.00 (± 12.00). A significant correlation was observed between knowledge and attitude (p < 0.05, r = 0.22) and between attitude and intervention (p < 0.05, r = 0.32), indicating a modest correlation. Moreover, a significant association was noted between years of experience and attitude and intervention (p < 0.05). Conclusion: Critical care nurses’ knowledge, attitudes, and interventions were poor; hence, they need to improve their knowledge, attitude, and interventions. The significance of sleep promotion and factors leading to critical care nurses in Malaysia not promoting sleep among ICU patients needs to be rectified. References: Acebedo-Urdiales MS, Medina-Noya JL, Ferré-Grau C. Practical knowledge of experienced nurses in critical care: a qualitative study of their narratives. BMC Medical Education. 2014 08 18;14(1). https://doi.org/10.1186/1472-6920-14-173 Alejandro J. Performance differences between novice and experienced critical care nurses: A replication study. 2013;. Tiruvoipati R, Mulder J, Haji K. Improving Sleep in Intensive Care Unit: An Overview of Diagnostic and Therapeutic Options. Journal of Patient Experience. 2020 Oct;7:697-702. Buntin M, Burke M, Hoaglin M, Blumenthal D. The Benefits Of Health Information Technology: A Review Of The Recent Literature Shows Predominantly Positive Results. Health Affairs. 2011 Mar;30:464-71. Chaudhry B, Wang J, Wu S, Maglione M, Mojica W, Roth E, Morton S, Shekelle P. Systematic Review: Impact of Health Information Technology on Quality, Efficiency, and Costs of Medical Care. Annals of Internal Medicine. 2006 May 16;144:742. Hahn R. Intensive care nurses' attitudes, beliefs and reported practices relating to patient sleep: A descriptive study (Master of philosophy thesis. 2018;. Nesbitt L, Goode D. Nurses perceptions of sleep in the intensive care unit environment: A literature review. Intensive and Critical Care Nursing. 2014 Aug;30:231-5. Andualem A, Asmamaw T, Sintayehu M, Liknaw T, Edmealem A, Bewuket B. Knowledge, attitude, practice and associated factors towards nursing care documentation among nurses in West Gojjam Zone public hospitals, Amhara Ethiopia, 2018. Clin. J. Nurs. Care Pract. J Nurs Care Pract. 2019;3:1-13. Ward N, Chong D. Critical care beds and resource utilization: Current trends and controversies. Semin Respir Crit Care Med. 2015 Dec;36:914-20. Mahran G, Taher A, Saleh N. Challenges and work crisis facing critical care nurses. Egypt Nurs J. 2017;14:235-41. Bion V, Lowe A, Puthucheary Z, Montgomery H. Reducing sound and light exposure to improve sleep on the adult intensive care unit: An inclusive narrative review. Journal of the Intensive Care Society. 2018 May;19:138-46. Czempik P, Jarosińska A, Machlowska K, Pluta M. Impact of Light Intensity on Sleep of Patients in the Intensive Care Unit: A Prospective Observational Study. Indian Journal of Critical Care Medicine. 2020 Jan;24:33-7. Gellerstedt L, Medin J, Kumlin M, Rydell Karlsson M. Nurses' experiences of hospitalised patients' sleep in Sweden: a qualitative study. Journal of Clinical Nursing. 2015 Dec;24:3664-73. Hopper K, Fried T, Pisani M. Health care worker attitudes and identified barriers to patient sleep in the medical intensive care unit. Heart & Lung. 2015 Mar-Apr;44:95-9. Gellerstedt L. Nursing perspectives on patients' sleep during hospital care. 2019;. Krejcie R, Morgan D. Determining Sample Size for Research Activities. Educational and Psychological Measurement. 1970;30:607-10. Zsarnay K. Critical care nurses' knowledge of sleep and sleep-promoting interventions. 1999;. Tavakol M, Dennick R. Making sense of Cronbach's alpha. International Journal of Medical Education. 2011 Jun 27;2:53-5. Skår R. Knowledge use in nursing practice: The importance of practical understanding and personal involvement. Nurse Education Today. 2010 Feb;30:132-6. Perrie H, Schmollgruber S, Bruce J, Becker P. Knowledge of intensive care nurses in selected care areas commonly guided by protocols. Southern African Journal of Critical Care. 2014;30:14. Liyew B, Tilahun D, Kassew A, T. Knowledge, attitude, and associated factors towards physical assessment among nurses working in Intensive Care Units: A multicenter cross-sectional study. Crit Care Res Pract. 2020 Aug 10. 2020;:9145105. Kirsch D, Harding S, Eichler A. Stages and architecture of normal sleep (Internet). 2022. 2021 September 19;. Romagnoli S, Villa G, Fontanarosa L, Tofani L, Pinelli F, De Gaudio A, Ricci Z. Sleep duration and architecture in non-intubated intensive care unit patients: an observational study. Sleep Medicine. 2020 Jun;70:79-87. Tamrat R, Huynh-Le M, Goyal M. Non-Pharmacologic Interventions to Improve the Sleep of Hospitalized Patients: A Systematic Review. Journal of General Internal Medicine. 2014 May;29:788-95. Tasew H, Mariye T, Teklay G. Nursing documentation practice and associated factors among nurses in public hospitals, Tigray, Ethiopia. BMC Research Notes. 2019 Sep 23;12:612. Stubberud D. Psychosocial needs in acute and critical illness. 2015;. Wells N, Pasero C, Mccaffery M. Improving the quality of care through pain assessment and management. Patient safety and quality: An evidence-based handbook for nurses. 2008;. Ramirez J. Developing a quality improvement project: Evaluating nurses' knowledge, perceptions, attitudes, and beliefs regarding sleep promotion in the ICU. 2017;. Li S, Wang T, Wu V, Liang S, Tung S, H. Efficacy of controlling night-time noise and activities to improve patients' sleep quality in a surgical intensive care unit. J Clin Nurs. 2011 Feb;20:396-407. Hsu W, Guo S, Chang C. Back massage intervention for improving health and sleep quality among intensive care unit patients. Nurs Crit Care. 2019 Sep;24:313-9. Elias C, Day T. Experiences of Newly Qualified Nurses in Critical Care: A qualitative systematic review. J Intensive Care Soc. 2020 Nov;21:334-43. Cortese C. Predictors of critical care nurses’ intention to leave the unit, the hospital, and the nursing profession. Open Journal of Nursing. 2012;02:311-26. Lamadah S, Sayed H. Risperidone Effectiveness with Attentional in Schizophrenic Patients. Journal of Biology, Agriculture and Healthcare. 2014;4:20-5. Bellon F, Mora-Noya V, Pastells-Peiró R, Abad-Corpa E, Gea-Sánchez M, Moreno-Casbas T. The efficacy of nursing interventions on sleep quality in hospitalized patients: A systematic review of randomized controlled trials. International Journal of Nursing Studies. 2021 Mar;115:103855. Wei Y. Health hazard evaluation report: HETA-93-0969-2389, St. Louis Post-Dispatch, St. Louis, Missouri.. 2020;. Asmirajanti M, Hamid AS, Hariyati RS. Nursing care activities based on documentation. BMC Nursing. 2019 Aug 16;18:32. Yuan C, Nembhard I, Kane G. The influence of peer beliefs on nurses' use of new health information technology: A social network analysis. Social Science & Medicine. 2020 Jun;255:113002. Blair W, Smith B. Nursing documentation: Frameworks and barriers. Contemporary Nurse. 2012 Jun;41:160-8. Alrebdi Y, Awadh AI, Alfehaid M, Alsindi A, Alaraj A. Knowledge and Attitude Regarding Sleep Medicine among Medical Students at Qassim University, Saudi Arabia. Open Access Macedonian Journal of Medical Sciences. 2019 Sep 14;7:2895-901. Dias S, Gama A, Cargaleiro H, Martins M. Health workers’ attitudes toward immigrant patients: a cross-sectional survey in primary health care services. Human Resources for Health.10. Rezaee N, Ghaljeh M, Salar A. Barriers to Providing High-Quality Nursing Care in Intensive Care Units: A Qualitative Study. Medical - Surgical Nursing Journal. 2020 Nov 21;9(3). https://doi.org/10.5812/msnj.110265 Almenyan AA, Albuduh A, Al-Abbas F. Effect of Nursing Workload in Intensive Care Units. Cureus. 2021 01 13;. https://doi.org/10.7759/cureus.12674 Radtke K, Obermann K, Teymer L. Nursing knowledge of physiological and psychological outcomes related to patient sleep deprivation in the acute care setting. Medsurg Nurs.. 2014;23(3):178-84. Farrehi PM, Clore KR, Scott JR, Vanini G, Clauw DJ. Efficacy of Sleep Tool Education During Hospitalization: A Randomized Controlled Trial. The American Journal of Medicine. 2016 Dec;129(12):1329.e9-1329.e17. https://doi.org/10.1016/j.amjmed.2016.08.001